(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Functions and the quality of wetlands have adversely been affected by factors such deforestation, fertilizers, and pesticides. Pollution caused by phosphates and nitrites affect aquatic life as these anions have serious side effects even at low levels. Wetlands are vital as they play a role to supply water used for domestic and farming. Pollution in wetlands leads to eutrophication, reduces dissolved oxygen among others. The objective of the study was to compare adsorption capacities of silica molybdate and diazonium silica with activated carbon. Silica molybdate was prepared by chlorination of raw silica then aminating using ethylenediamine (EDA) followed by addition of sodium molybdate to aminated silica. Diazonium silica was prepared by reacting aminated silica with sodium nitrite. FT-IR spectroscopy was used characterize the prepared adsorbents. The adsorption capacities of the adsorbents was compared with activated carbon. The adsorbents were used to remove PO43- and NO2- ions from water collected from wetlands. FT-IR results showed adsorption bands at 854cm-1 and 542cm-1 attributed to Mo=O and Mo-O stretching in molybdate. Diazonium silica showed a spectra band at 1587 cm-1 assign to open chain azo (N=N) group. Biosorption isotherm fitted well in Freundlich isotherm model for adsorption of phosphates. Biosorption isotherm model that fitted well for adsorption of nitrites was Langmuir model. For sorption of phosphates pseudo-first order kinetics model was best obeyed while for adsorption of nitrites pseudo-second order kinetic model was best obeyed. Adsorption capacity of phosphate was 194.53mg/g and 6.892 mg/g for nitrites as compared to activated carbon which was 8.241 mg/g for phosphates and 0.07985 mg/g for nitrites. For adsorption of nitrites biosorption isotherm fitted well in Langmuir model. For sorption of phosphates pseudo-first order kinetics model was best obeyed while for adsorption of nitrites pseudo-second order kinetic model was best obeyed. Adsorption efficiency of phosphates and nitrites in wetland waters, were 55.9% for phosphates and 44.7% for nitrites.Results obtained indicate that silica molybdate and diazonium silica are better adsorbents as compared to activated carbon.